Hypoxia-inducible factor-1α/vascular endothelial growth factor signaling pathway–based ulcer-healing mechanism of Astragalus Aqueous extract in diabetic foot rats: Astragalus aqueous extract promoted DF ulcer wound healing - Jia, Xuxu; Yang, Juan; Guo, Qian; Ni, Honggang; Yu, Yujie; Dai, Jingrun; Jiang, Mei (Cellular and Molecular Biology, 2024)
The main objective of this work was to investigate the mechanism of Astragalus aqueous extract ulcer healing in diabetic foot model rats through the hypoxia-inducible factor 1-alpha (HIF-1ɑ)/vascular endothelial growth factor (VEGF) signalling pathway. Fifty specific-pathogen-free male Sprague Dawley rats were divided into blank (A), model control (B), Astragalus extract (C) and mupirocin (D) treatment groups. Group A received a regular diet, whereas the other groups received a high-fat/high-sugar diet and intraperitoneal streptozotocin injections to induce diabetes. Diabetic foot ulcers were created via skin excision. Subsequently, ulcers were debrided daily. Groups B, C and D received wet saline gauze, wet gauze with Astragalus extract and gauze with mupirocin, respectively, on the affected area. Group A received no treatment. After 14 days, the rats were assessed for ulcer healing and general condition. Immunohistochemistry was used to detect HIF-1ɑ and VEGF levels in the dorsalis pedis artery, and ELISA was used to determine serum IL-6 and CRP levels. The results revealed that Groups C and D had significantly faster ulcer healing compared with Group B (p < 0.01), and ulcer healing was faster in Group C than in Group D (p < 0.01). Group C exhibited notably higher HIF-1ɑ and VEGF protein expression levels compared with Groups B and D (p < 0.01). IL-6 and CRP expression levels in Groups C and D were significantly lower than those in Group B (p < 0.01). In summary, Astragalus aqueous extract effectively treats diabetic foot ulcers by up-regulating HIF-1ɑ and VEGF expression, activating the HIF-1ɑ/VEGF pathway, improving local tissue ischaemia and hypoxia, promoting collateral circulation and enhancing dorsalis pedis artery formation, thereby accelerating ulcer repair in diabetic rats.